PEMANFAATAN MEDIA SOSIAL FACEBOOK SEBAGAI STRATEGI KOMUNIKASI POLITIK DALAM MEMBENTUK CITRA POLITIK (STUDI KASUS DI KABUPATEN PENAJAM PASER UTARA) - Rosmini Rosmini; Syamsu Rizal; Andi Vita Sukmarini (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2024)
Political communication is placed as the study of political science because the messages conveyed in the communication process are politically characterized. In political communication, a strategy is needed to support the success of political communication. This study aims to determine and describe the use of Facebook social media as a political communication strategy in shaping the political image of the PPU PAN DPRD Candidate. The problems in this research were analyzed using a qualitative research approach with the data and information used, obtained from observations and in-depth interviews. Based on the analysis conducted, it can be seen that the communication strategy applied by PAN involves a direct and responsive approach to community needs, especially in the context of visits to sick residents' homes. This strategy includes two main elements. PAN uses a personal and empathetic approach to build emotional bonds with the community, and at the same time strengthen the party's image as an entity that cares about social issues, especially public health. Then for the use of Facebook social media, PAN PPU is still not optimal. However, awareness of the importance of social media already exists so that in the future the use of social media will be more optimized.